Will the Doha Round Lead to Preference Erosion? - Romalis, John (IMF Working Papers; Working Paper ;, 2006)
This paper assesses the effects of reducing tariffs under the Doha Round on market access for developing countries. It shows that for many developing countries, actual preferential access is less generous than it appears because of low product coverage or complex rules of origin. Thus lowering tariffs under the multilateral system is likely to lead to a net increase in market access for many developing countries, with gains in market access offsetting losses from preference erosion. Furthermore, comparing various tariff-cutting proposals, the research shows that the largest gains in market access are generated by higher tariff cuts in agriculture.